Autonomous navigation robot using slam and path planning based on a Single RP-LIDAR - Abu Ubaidah, Shamsudin; Puteri Alisha Balqis, Mohd Sharif; Soomro, Zubair Adil; Ruzairi, Abdul Rahim; Ahmad Athif, Mohd Faudzi; Wan Nurshazwani, Zakaria; Mohamad Heerwan, Peeie; Salaan, Carl John O. (Semarak Ilmu Publishing, 2025)
This paper proposes an autonomous robotics system based on a single LIDAR sensor for delivering goods. There are needs to deliver goods such as medical supplies to the hospital and document in office. Although this task is simple, the delivery task is time consuming, tedious, and boring. In this regard, autonomous robotic systems could be a suitable solution. Here-in, we proposed the use of a single RP-LIDAR sensor in a robotic system that is sufficient for delivering goods in indoor environment. The robotic system uses autonomous navigation module which consists of simultaneous localization and mapping (SLAM) of the environment, and path planning for the robot to move safely from its current location to a desired position. In the context of SLAM, Hector SLAM method was opted due to its capability to harness sufficient data from a single LIDAR sensor. When it comes to path planning, the system employs a two-pronged approach. First, a global planner, utilizing the A* algorithm, facilitates long-distance trajectory planning while accounting for static obstacles. Second, a local planner, employing the Trajectory Rollout and Dynamic Window Approach (DWA), ensures real-time obstacle avoidance in the presence of moving obstacles. The approach was evaluated in a laboratory environment (11 meter by 8 meter) and successfully built a path that avoided obstacles in both static and dynamic conditions. This approach for autonomous robotics using a single RP-LIDAR sensor has the potential to revolutionize the delivery industry and other sectors that require autonomous navigation.